Ethnic Identity In Political Communication: A Case Study In Teluk Pulai Village, Kualuh Leidong Sub-District - Nasution, Dakli; Paralihan, Hotmatua (Academy of Education Journal, 2025)
This research aims to analyse the influence of ethnic identity in political communication in Teluk Pulai Village, Kualuh Leidong Sub-district, Labuhanbatu Utara Regency. Using a qualitative approach and case study method, data was collected through participatory observation and in-depth interviews with community leaders, village heads, and residents from various ethnicities. The results show that political communication in Teluk Pulai Village shows that ethnic identity becomes social and symbolic capital in strengthening community cohesion. Traditional and political leaders utilise culture, language, and traditional rituals to build legitimacy and emotional closeness. Informal communication and cultural symbols are effective in conveying political messages. However, unwise ethnic politicisation risks divisiveness, so inclusive, dialogic and contextualised political narratives are needed to maintain unity and democratic participation. While the politicisation of ethnic identity can lead to social fragmentation, inclusive, dialogue-based political communication across ethnic lines strengthens social cohesion and the legitimacy of local leaders. This study confirms the importance of integrating socio-cultural aspects in political communication to support democracy and stability in coastal multiethnic societies